2009
DOI: 10.1016/j.jbankfin.2009.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Do financial factors affect the capital–labour ratio? Evidence from UK firm-level data

Abstract: This paper investigates the nexus between financial factors and the capital-labour ratio using a rich firm-level data set. It is common in the literature to examine the impact of financial constraints on hiring and firing decisions separately from their impact on decisions related to investment in physical capital. We argue that as long as firms use both inputs in production and there is some substitutability between them, the two decisions need to be jointly analyzed. When we differentiate across firms that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 42 publications
1
29
0
1
Order By: Relevance
“…1 This finding is in line with previous evidence (see Spaliara (2009)) which shows that more constrained firms exhibit greater sensitivities of the K/L ratio to financial variables. Turning to the result of our main interest, we now focus on the differential effect of financial variables on the K/L ratio for small firms.…”
Section: Econometric Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…1 This finding is in line with previous evidence (see Spaliara (2009)) which shows that more constrained firms exhibit greater sensitivities of the K/L ratio to financial variables. Turning to the result of our main interest, we now focus on the differential effect of financial variables on the K/L ratio for small firms.…”
Section: Econometric Resultssupporting
confidence: 86%
“…Guariglia (2008) and Nickell and Nicolitsas (1999) find significant effects of financial constraints on UK firms' fixed investment and employment choices. Recently, Spaliara (2009) considered the effects of financial indicators on both investment and hiring decisions to examine how financial constraints affect the allocation of funds between capital and labour when decisions on both inputs have to be taken simultaneously rather than 1 independently. Results show that financially constrained firms face a greater sensitivity of the K/L ratio to financial characteristics compared with their unconstrained counterparts.…”
Section: Introductionmentioning
confidence: 99%
“… MacKay and Phillips (2005) and Spaliara (2009) have also confirmed that firm‐specific factors, rather than industry characteristics, are important for explaining inter‐firm K / L variations. …”
mentioning
confidence: 81%
“…This has the advantage of restricting the efficiency measures in the 0-1 range and hence facilitates comparisons with more conventional -e.g., Shephard type efficiency measures where a fully efficient firm has a score of 1. 9 Highly levered firms may face financing constraints that will prevent them from adjusting their capital to labor ratios and thus attain more efficient production allocations (see Spaliara, 2009). Debt financing may also have a negative effect on firm performance for firms with plentiful growth opportunities (see Myers, 1977;Jensen, 1986;McConnell and Servaes, 1995).…”
Section: Firm Performancementioning
confidence: 99%